Implementation of the STAD Cooperative Learning Model on Student Learning Activities - Sari, Tri Maniarta; Rismayanti , Rismayanti; Arya Fitra , Rahmat; Ernawati, Ernawati; Pamungkas, Rahmania (BIODIK, 2024)
The learning that occurs at SMP Negeri 1 Tinondo is still not student-centered so that many students are still passive when learning takes place. Therefore, it is necessary to apply a learning model that can increase student learning activities and student participation in learning, one of which is the STAD cooperative learning model. This research aims to determine the influence of the Student Team Achievement Division (STAD) learning model on the activities and science learning outcomes of Class VIII students at SMP Negeri 1 Tinondo. The type of research used in this research is Quasy Experimental research. The total population in this study was 48 class VIII students at SMP Negeri 1 Tinondo. The sample used in this research consisted of two classes, namely: experimental class (Class VIII A with 24 students), and control class (Class VIII B with 24 students). With a Control Group Pretest-Posttest Design research design. The instrument used was an observation sheet on the implementation of syntax and student learning activities. The research results showed that, from 48 class VIII students at SMP Negeri 1 Tinondo for learning activities, the average score for the experimental class was 65.05 in the fair category, while for the control class it was 53.24 in the not good category. Based on the research results, it can be concluded that the Student Team Achievement Division (STAD) learning model can influence science learning activities and outcomes at SMP Negeri 1 Tinondo.